ANALISIS KESALAHAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP - Septi Nur Rizki; Nesi Septiani; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This research was conducted with the aim of knowing the mathematical creative thinking skills of junior high school students in one of the state junior high schools in West Bandung district that has implemented the 2013 curriculum with the research subjects of grade VII students as much as one class. The indicators used in students' mathematical creative thinking are fluency, flexibility, authenticity or originality, and detail or elaboration. The ability to think creatively is the ability to think with the aim of generating new ideas or various answers to a problem by paying attention to the quantity of answers and the quality of the solution. The test instrument used was written as many as five essay questions. The method used in this study is a qualitative descriptive research method. With data processing techniques through data tabulation, then calculated percentage then interpreted. The conclusions from the results of this study indicate that mathematical creative thinking of junior high school students in one of the state junior high schools in the area of West Bandung Regency is classified as moderate.